Preferences, Selection, and Value Added: A Structural Approach Applied to Turkish Exam High Schools - S. Pelin Akyol; Verónica Frisancho; Kala M. Krishna; Cemile Yavas (Center for Economic Studies and ifo Institute (CESifo), 2013)
What do applicants care about when choosing a school in Turkey? Are their preferences vertical or horizontal? Which school attributes seem to matter? Do selective schools con-tribute to their students' success, or is their performance attributable to the higher ability of the students they accept? By taking a structural approach we answer all these questions in one go. We find that students seem to infer quality from past performance in the University entrance exam. There also seems to be a consumption value of attending elite schools and schools add very different value and this is unrelated to their selectivity.
Keywords: I20; I21; 330